Implementation of al-Attas’s Islamization on the Impact of Desacralization of Politics - Pramono, Muhamad Fajar; Sahidin, Amir (Center of Islamic and Occidental Studies, 2023)
Desacralization of politics is a thought born from a Western secular perspective, aiming to separate religion from politics. It has a bad influence on human life both in epistemologically and methodologically aspects. In addition, this thought also had an impact and was adopted by Muslim scholars, one of which was Ali Abdul Raziq in his secular political theory. Ali argues that